Attitude, time management work-life balance and career choices: a mediating effect of protean career attitude among medical students in Malaysia - Ainer, Chitra Devi; Musa, Siti Nur Syuhada; Hamzah, Siti Raba’ah; Md Tamrin, Shamsul Bahri; Abdul Aziz, Mohd Faiq (Human Resource Management Academic Research Society, 2024)
A thorough empirical approach to protean career attitude as a mediator has yet to be completely established, even though the relevance of this variable has been explored in the career management field for the past three decades. Most research looked at how a protean career functions as an independent variable and how it interrelates with other dependent variables such as career success, organizational commitment, employability, HRD practices, career mobility and career strategies. Due to this, our study examined the influence of the predictors such as protean career attitude, attitude, work-life balance, and time management towards career choices. This study also examines the mediating role of protean career attitude. With the support of social cognitive career theory and life-span, life-space theory, this study sought to determine the contribution of individual factors towards career choices. The respondents for this study are medical students from public universities in year 1 through year 5. This research used the descriptive and correlation design for quantitative research. This study uses a questionnaire to collect the data. The data were further analyzed using the Statistical Package for the Social Sciences (SPSS) version 26. The results showed that the mediating effect of protean career attitude has an influence on attitude and time management and no influence on work-life balance towards career choices. This research is significant as the findings contribute to the body of knowledge in developing research framework and enhances the knowledge of individual career choices, organizational practices, government policy, and theoretical development.